ДРАМАТА КАКО СЦЕНСКА МЕТАФОРА (Filološke pripombe, 2019)
In this article the author writes about the circumstances in Macedonian drama and theatre in the seventies of the twentieth century with particular reference to the work of Branko Pendovski. He uses mythical and archetypal symbolism to depict reality in a way that corresponds to the developments in European drama, such as existentialism, epic theatre and tragic farce. Such an approach to dramatic material makes Branko Pendovski a prominent figure in Macedonian literature. In his plays he favours a deliberate approach to all elements that make up the play and their integration into a complete system.